Flexible ability-willingness trade-offs in cooperative partner choice: Evidence from a drift-diffusion model and ERP data - Qiang Xu; Jing Wang; Jing Wang; Peng Li (NeuroImage)
Partner choice plays a crucial role in human social behavior, with previous research highlighting the importance of both partner ability and willingness to cooperate in decision-making processes. However, the dynamic interplay between these factors across different contexts and how they are influenced by individual characteristics remain poorly understood. This study investigated how task demands and individual traits modulate the tradeoff between partner ability and willingness to make social decisions. We employed a novel experimental paradigm combining three tasks (prisoner's dilemma, time estimation, and a combined task) with computational modeling and EEG recording. Fifty-three participants completed partner-selection trials across these tasks, while their behavioral and neural responses were recorded. Drift diffusion model (DDM) analysis revealed that decision weights for partner ability and willingness were systematically modulated by task demands, with willingness prioritized in cooperative contexts, but ability prioritized in skill-based tasks. Using these model-estimated weights, we found that participants with high self-perceived ability had higher ability weights, whereas those with high self-perceived willingness had lower ability weights in their decision making. EEG analysis, utilizing trial-level weights computed by the DDM, showed that the processing of willingness and ability information began approximately 300 ms post-stimulus, with distinct spatiotemporal patterns across tasks. In the combined task, EEG data indicated earlier and more extensive processing of willingness than of ability information. These findings reveal that individuals flexibly adjust their weighting of partner willingness and ability based on task demands, challenging the notion of a fixed ''willingness priority'' and demonstrating the dynamic nature of social decision-making across contexts.